Coronavirus Disease 2019 and Diabetes: The Epidemic and the Korean Diabetes Association Perspective - Junghyun Noh (Diabetes & Metabolism Journal, 2020)
Diabetes has been associated with more severe outcomes and higher mortality in coronavirus disease 2019 (COVID-19) patients compare to morbidity and mortality in patients without diabetes. Several mechanisms may play a role in this greater morbidity and mortality, especially uncontrolled hyperglycemia, an impaired immune system, pre-existing proinflammatory states, multiple comorbidities, and dysregulated angiotensin-converting enzyme 2 signaling. Thus, the diabetes medical community emergently needs to know about COVID-19 and its effects on patients with diabetes, as they must take precautions to carefully manage these patients during the COVID-19 pandemic. The Korean Diabetes Association provides some guidance and practical recommendations for the management of diabetes during the pandemic. This report provides insight into the association between diabetes and COVID-19, proper management of diabetes in patients with COVID-19 and an official suggestion by the Korean Diabetes Association for managing the COVID-19 outbreak.